DEVELOPMENT OF THE TAM MODEL OF FACTORS THAT INFLUENCE THE ACCEPTANCE OF MOBILE PAYMENTS - Berisca, Adithero; Clive, Stephen; Hardani, Jauharil Achsan; Hutabarat, Anthonius S (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to develop a Technology Acceptance Model (TAM) specifically for Mobile Payment use in the public transportation environment, with a focus on users of the Jakarta MRT. The research examines the factors that influence acceptance of Mobile Payment in the city transportation context, using a quantitative survey approach of Jakarta MRT users. The study analyzed the factors underlying TAM, which includes perceived usefulness, perceived ease of use, as well as other variables that can influence Mobile Payment acceptance. The research findings will offer a deeper understanding of the determinants of Mobile Payment acceptance in public transportation and contribute to the existing literature applying the TAM model to Mobile Payment in Indonesia. The results of this study could serve as a basis for enhancing the efficiency and adoption rates of Mobile Payment systems among users of public transportation, particularly in the Jakarta MRT and other similar systems in the future.